The effect of motivation and compensation on employee’s work satisfaction. Case study of PT Infomedia Nusantara Telkomsel E-Care Division - Rosenda, Rossa; Tarmidi, Didi (Technium Social Sciences Journal, 2021)
This study aims to determine how the description of employee motivation, compensation, and job satisfaction, as well as to determine how motivation and compensation affect the job satisfaction of PT. Infomedia Nusantara Telkomsel E-Care Division. The factors tested in this study were motivation and compensation as independent variables, while job satisfaction was a dependent variable. The research methods used in this study are descriptive and verification methods. The population in this study was employees at PT. Infomedia Nusantara Telkomsel E-Care Division. The sampling technique used in this study is Purposive Sampling and the size of the samples in this study is calculated by slovin formula, so the total number is 133 respondents. The analysis methods used in this study are some linear regression analysis using SPSS25 for Windows. The results of this study showed that motivation and compensation have an effect on employee job satisfaction at PT. Infomedia Nusantara Telkomsel E-Care Division. The amount of work motivation and compensation on employee job satisfaction was 26.1%.